(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: The most important guarantee for the success of the health system transformation plan is paying attention to health care providers, including nurses. The purpose of this study was to determine the job satisfaction of nurses who were affected by the implementation of a health system transformation plan. Methods: This study is a descriptive study. In this study, the research population included all nurses in wards working in Rouhani Hospital in 2019. The sampling method is the census; the sample size of this study is 70 people; the research tool is the Spector Job Satisfaction Questionnaire (36 questions). In terms of validity, the questionnaires were evaluated by experts, and their reliability reported a Cronbach’s alpha of 0.88 for this tool. Also, the data analysis method will be introduced in SPSS statistical software version 22, and the necessary analysis is done. Findings: The results showed that there was a significant relationship between nurses’ viewpoints about the impact of a health system transformation plan on their job satisfaction (significance level less than 0.05). Conclusion: By implementing health plan transformation, their job satisfaction is at an acceptable level, which can have a positive impact on their performance and can lead to greater satisfaction for patients and their families.